Integrating the Concept of Plane Figure and Baduy Local Wisdom as a Media Alternative of Mathematics Learning In Elementary Schools - Arisetyawan, Andika; Taher, Tarmizi; Fauzi, Irfan (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2021)
This study aims to develop a learning media product that contains the local wisdom of the Baduy tribe. The method used in this research is an ethnographic study to collect data about the Baduy tribe buildings that contain geometric elements. After the data was collected, the researcher used the instructional design research method in the form of the ADDIE model with the aim of making learning media by integrating the local wisdom of the Baduy Tribe in learning geometry based on previous ethnographic studies. The subjects in this study were the Baduy people, teachers, and grade 4 students of one of the elementary schools in Serang City. The results of this study indicate that learning geometry by integrating the local wisdom of the Baduy tribe is very effective in the learning process, so that the learning media product in the form of geomatics cards that are made is ready to be used and implemented in the concept of the plane figure in elementary schools. This research is expected to contribute to education, especially in creating effective learning by integrating culture in mathematics learning in elementary schools.Penelitian ini bertujuan untuk mengembangkan sebuah produk media pembelajaran yang memuat kearifan lokal suku Baduy. Metode yang digunakan dalam penelitian ini adalah studi etnografi untuk mengumpulkan data-data tentang bangunan suku Baduy yang memuat unsur geometri. Setelah data terkumpul, peneliti menggunakan metode instructional design research berupa model ADDIE dengan tujuan untuk membuat media pembelajaran dengan mengintegrasikan kearifan local Suku Baduy pada pembelajaran geometri berdasarkan kajian etnografi sebelumnya. Subjek dalam penelitian ini adalah masyarakat Suku Baduy, guru dan siswa kelas 4 salah satu sekolah dasar di Kota Serang. Hasil penelitian ini menunjukkan bahwa pembelajaran geometri dengan mengintegrasikan kearifan local Suku Baduy sangat efektif diterapkan dalam proses pembelajaran, sehingga produk media pembelajaran berupa kartu geomatika yang dibuat telah siap digunakan dan diimplementasikan padaÂ konsep bangun datar di sekolah dasar. Penelitian ini diharapkan dapat memberikan kontribusi dalam dunia pendidikan khususnya dalam menciptakan pembelajaran yang efektif dengan mengintegrasikan budaya pada pembelajaran matematika di sekolah dasar.